Three-dimensional electroanatomical mapping guidelines for the selection of pacing site to achieve cardiac resynchronization therapy - Hua, Bao-Tong; Pu, Li-Jin; Tian, Xin; Song, Wen-Juan; Li, Hao; Wang, Chao; Shao, Xiao-Xia; Li, Rui; Li, Shu-Min; Li, Zhi-Xuan; Zou, Jun-Hua; Zhao, Ling; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives We aimed to evaluate the feasibility of left ventricular electroanatomical mapping to choose between left bundle branch area pacing (LBBAP) or coronary venous pacing (CVP). Background There are several ways to achieve left ventricular activation in cardiac resynchronization therapy (CRT): LBBAP and CVP are two possible methods of delivering CRT. However, the criteria for choosing the best approach remains unknown. Methods A total of 71 patients with heart failure, reduced ejection fraction, and left bundle branch block (LBBB) were recruited, of which 38 patients underwent the three-dimensional electroanatomical mapping of the left ventricle to accurately assess whether the left bundle branch was blocked and the block level, while the remaining 33 patients were not mapped. Patients with true LBBB achieved CRT by LBBAP, while patients with pseudo-LBBB achieved CRT by CVP. After a mean follow-up of 6 months and 1 year, the QRS duration and transthoracic echocardiography, including mechanical synchrony indices, were evaluated. Results Twenty-five patients with true LBBB received LBBAP, while 13 without true LBBB received CVP. Seventeen patients received LBBAP, and 16 patients received CVP without mapping. Paced QRS duration after the implantation of LBBAP and CVP was significantly narrower in the mapping subgroup compared to the non-mapping subgroup. A significant increase in post-implantation left ventricular ejection fraction was observed in patients with LBBAP or CVP, and the mapping subgroup were better than the non-mapping subgroup. After a 12-month follow-up, atrioventricular, intraventricular, and biventricular synchronization were significantly improved in the mapping subgroup compared to non-mapping groups in both LBBAP and CVP. Conclusion In our study, three-dimensional electroanatomical mapping was used to choose LBBAP or CVP for heart failure patients, which proved feasible, with better cardiac resynchronization in the long-term follow-up. Therefore, three-dimensional electroanatomical mapping before CRT appears to be a reliable method for heart failure patients with LBBB who are indicated for CRT.